Ripple in still water when there is no pebble tossed: Festschrift in honour of Cary J. Martin - Almásy-Martin, Adrienn; Chauveau, Michel; Donker van Heel, Koenraad; Ryholt, Kim (Egyptology, 2022)
This Festschrift in honour of Cary J. Martin presents twenty contributions of his friends and colleagues, ranging from articles on Persian and Graeco-Roman Egypt to twenty-two (re-)editions of documentary and literary texts written in Egyptian (Hieroglyphs, Hieratic and Demotic) and Greek. Many of them here published for the first time